This is an Inverse.
Final Answer : A
This is because each part (the hypothesis and conditional) were reversed.
Answer:
2x +3y=1⇒equation 1
3x=2y+8
3x-2y=8⇒equation 2
by elimination method,
2x+3y=1 ×2
3x-2y=8 ×3
4x+6y=2
9x-6y=24
cut 6y and -6y
4x+6y=2
9x-6y=24
---------------
13x+0=26
13x=26
x=26/13
x=2
substitute x=2 in equation 1
2(2)+3y=1
4+3y=1
3y=1-4
3y=-3
y=-3/3
y=-1
therefore, x=2 and y=-1
hope it helps u!
The answer is 58 because 65 -7 = 58 so i help u in help on a other thing i have the answer!
Answer:
I got a decimal
Step-by-step explanation:
<u><em>0.857142857</em></u>